Response of wet-season rice (Oryza sativa) to nitrogen and phosphorus in partially reclaimed sodie soil - RAM, S; CHAUHAN, R P S; SINGH, B B; SINGH, V PAL (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted in rainy season (kharif) of 1993 and 1994 at Faizabad to find out the nitrogen and phosphorus requirements of wet-season rice (Oryza sativa L.) in partially reclaimed sodic soil. Nitrogen @ 120 kg/ ha for rice in normal soil was enough fbr growing the crop in partially reclaimed conditions, Phosphorus @ 13 kg P/ha (half the dose for rice in normal soil) yielded grain and straw at par with 26 and 39 kg P/ha. Response equations for nitrogen and phosphorus were worked out. The economic optimum for nitrogen was 86.8 kg N/ha and for phosphorus 27 kg/ha. The quality of grains for protein and mineral composition at 120 kg N/ha and at 13 kg P/ha was equivalent to that at 180 kg N/ha and 26 and 39 kg P/ha respectively. Application of N and P also improved the physico-chemical properties of sodic soil due to better root development in general.